2017
DOI: 10.1021/acs.jnatprod.7b00650
|View full text |Cite
|
Sign up to set email alerts
|

Jozilebomines A and B, Naphthylisoquinoline Dimers from the Congolese Liana Ancistrocladus ileboensis, with Antiausterity Activities against the PANC-1 Human Pancreatic Cancer Cell Line

Abstract: Two new naphthylisoquinoline dimers, jozilebomines A (1a) and B (1b), were isolated from the roots of the Congolese plant Ancistrocladus ileboensis, along with the known dimer jozimine A (2). These compounds are Dioncophyllaceae-type metabolites, i.e., lacking oxygen functions at C-6 and with an R-configuration at C-3 in their tetrahydroisoquinoline moieties. The dimers 1a and 1b consist of two 7,1'-coupled naphthylisoquinoline monomers linked through an unprecedented 3',6″-coupling in the binaphthalene core a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 67 publications
2
56
0
Order By: Relevance
“…In the data gathered in Table 4, as previously commented, it can be observed that even in the same plant species and same organ, different compounds have been characterized like jozilebomines and dioncophyllines in Ancistrocladus ileboensis leaves (J. Li et al, 2017d;J. Li et al, 2017c) or xanthohumol and a-acid derivatives such as humulones in Humulus lupulus flowers (J.…”
Section: Zizyphus Jujubamentioning
confidence: 71%
“…In the data gathered in Table 4, as previously commented, it can be observed that even in the same plant species and same organ, different compounds have been characterized like jozilebomines and dioncophyllines in Ancistrocladus ileboensis leaves (J. Li et al, 2017d;J. Li et al, 2017c) or xanthohumol and a-acid derivatives such as humulones in Humulus lupulus flowers (J.…”
Section: Zizyphus Jujubamentioning
confidence: 71%
“…In view of the promising anti‐infective activities of some dimeric naphthylisoquinolines,,, the new products were tested against the protozoan parasites causing malaria, African sleeping sickness, and leishmaniasis. Most remarkable was the excellent antiplasmodial activity of 17 against the chloroquine‐resistant K1 strain of Plasmodium falciparum in vitro (IC 50 =0.003 μ M), combined with a very low cytotoxicity (IC 50 =62.26 μ M), making a selectivity index of more than 20,000 – better than any mono‐ or dimeric naphthylisoquinolines ever tested ,…”
Section: Resultsmentioning
confidence: 99%
“…They consist of a naphthalene and an isoquinoline portion, both derived from polyketide precursors,, linked together by a biaryl axis that is, in most cases, rotationally hindered and, thus, stereogenic. Depending on their individual structures, they have pronounced anti‐infective or antitumoral activities ,. More than 200 representatives of this unique class of natural products have so far been isolated, among them more than 20 dimers, which possess even three biaryl axes ,.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 In brief, exponentially growing cells were harvested and plated in 96-well plates (2 Â 10 3 per well) in DMEM and allowed to attach for 24 h in the humidied CO 2 incubator at 37 C. The cells were then washed with phosphate-buffered saline (PBS) followed by the addition of serially diluted test samples in DMEM. For each concentration, three replications were performed.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%